KEKERASAN SIMBOLIK PADA PROGRAM ACARA FESBUKERS RAMADAN 2017 DALAM SEGMEN RUMAH MIRING (RUMING) EDISI BUKA PUASA - FIRDA YAHYA; MUHAMMAD YUSUF AR (Fakultas Dakwah dan Komunikasi, 2018)
Symbolic violence is not physical or psychological violence. If these two forms of violence can be easily recognized, symbolic violence is very difficult to recognize. Symbolic violence can occur at any time and without realizing it. The purpose of this study is to find out the symbolic violence that is present in the program